A Relação bilateral Brasil-Estados Unidos durante os governos de Fernando Henrique Cardoso (1995-2002): análise da ALCA - Monteiro, Nara Marques (2020)
The objective of this research is to analyze the bilateral relationship between Brazil and the United States, having as a time frame the two governments of President Fernando Henrique Cardoso (1995 to 2002). The main focus will be to understand the Brazilian position considering political, diplomatic, economic and conjunctural variables. It is understood that the relationship involving these two countries is historical, and Brazil's search for insertion in the international dynamics directs its performance in international relations, in this sense strategic relations are characteristic and substantial to achieve this goal. The purpose of this work is, fundamentally, to understand the nature of this relationship and to analyze Brazil's position in the Free Trade Area (FTAA). The initial hypothesis used is that in the government in question, the relationship with the U.S. conditioned decisive aspects of Brazilian foreign policy. Therefore, to test the hypothesis, an qualitative analysis of the Brazilian positions in relation to the FTAA negotiations will be made through the bibliographic and documentary review covering documents available at a primary level and also bibliographical material. Based on this hypothesis, it is observed that the decision-making in the PEB was linked to the United States' agenda, the argument used is that the relationship with the North American country could generate gains for the development sought by the Brazilian government at that time